THE EFFECT OF MUDHARABAH FINANCING ON THE PROFITABILITY OF ROA AND ROE OF SHARIA RURAL BANKS (BPRS) IN INDONESIA 2017-2018 - Khansa Asy-Syaffa; Nur S Buchori; Firmansyah Firmansyah (Sekolah Tinggi Ekonomi Islam (STEI) SEBI, 2020)
The purpose of this research is to analyze The Influence of Mudharabah Financing as the dependent variable (X) To The Return On Asset (ROA) as independent variables (Y1) and Return On Equity (ROE) as independent variables (Y2), of The Sharia Rural Banking (BPRS) in Indonesia in 2017-2018. This analysis used 106 BPRS that are made as a sample. The data sources used are secondary data sources from reports on financial publications of each Syariah Rural Banking at the OJK. This type of research is quantitative with Cross Section data method. The analysis technique used is the Eviews 10 for students. The results of this study indicate that Mudharabah Financing has no significant effect on the Ratio On Asset with a regression coefficient and a significance level of 0,16more than 0.05. While Mudharabah Financing has no significant effect with the regression coefficient of 0,16 with a significance level 0,00 less than 0.05